Implementação da política educacional para educação primária em Cuba: adesão e discricionariedade - Palitot , Katianne Cristina dos Santos (2020)
This research aimed to investigate the implementation of public educational politics in the early years of basic education in Cuba. As a theoretical framework, it was based on studies on the implementation of a public policy, adopting as main theoretical frameworks Lipsky (1980), Arretche (2001) and Lotta (2010). According to these authors, the implementation of public politic can be understood as a part of the politic in which the actors of the implementation process interact with each other and with the beneficiaries, offering public services according to official guidelines and also their values and beliefs. For the study, questionnaires were applied to 27 Cuban teachers from the early years of elementary school. For data analysis and content analysis, we relied on the notes by Bardin (1977) and Breches et al (2019). Previous categories were defined from the literature, and the data were classified seeking relevance of content to the previous categories: adherence, discretionary and implementation conditions (favorable and unfavorable factors) The research concludes that there is the use of discretionary in the implementation of educational politics in the early years of basic education in Cuba, especially regarding to the necessary adaptations of the curriculum due to the scarcity condition. We also found that adherence to the implementation process occurs by the implementing agents and this is described by teachers in their daily practice. The interviewees consider that the factors that favor the implementation of the policy are related to external factors, more specifically to the economic blockade imposed on the country, which has been affecting Cuban education not only with scarcity of material resources, but also of human resources due, according to the teachers, low wages. The questionnaires also reveal that the initial training of teachers, the evaluations carried out to guide the individual practices of educational institutions, the quality and structure of education and the commitment of professionals are perceived by teachers as factors that favor the implementation of educational policy for the early years of elementary school.